Conscious and Unconscious Mentality Examining their Nature, Similarities and Differences - Hvorecký, Juraj; Marvan, Tomáš; Polák, Michal (Taylor & Francis, 2024)
attention; higher-order theories of consciousness; inattentional blindness; masking; mental qualities; neurophenomenal structuralism; phenomenal content; unconscious mental states